SYSTEMATIC LITERATURE REVIEW (SLR) : PENGGUNAAN BAHASA INDONESIA YANG BAIK DAN BENAR DALAM KEHIDUPAN SEHARI – HARI - Raisya Rhadella Br Ginting; Usiono Usiono (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study explores the good and correct use of Indonesian in daily life, by highlighting various problems faced by the community in applying language rules. In particular, the main issues raised include a lack of understanding of correct grammar and vocabulary, as well as the impact of the use of social media that often ignores the rules of formal language. The main objective of this study is to analyze the appropriate use of Indonesian in various social contexts, as well as to evaluate how the application of language rules can affect the effectiveness of communication. Thus, this study aims to provide insight into the importance of good language use in daily interactions. The research method used is Systematic Literature Review (SLR), which allows researchers to identify, review, and analyze relevant literature sources. Searches are conducted in academic databases with related keywords, and the selected articles include research published within a specific time span, thus providing a comprehensive overview of the topic. The results of the study show that there are several important factors that affect the good use of Indonesian, including understanding of grammar rules, choosing the right vocabulary, and the influence of social media which often causes deviations from the correct language rules. The discussion showed that effective language education can help increase public awareness of the importance of good language use, as well as provide recommendations for the development of language education curricula that are more relevant to the modern context. The novelty of this study lies in the merger of traditional and modern perspectives in the use of language, as well as the emphasis on the need to adapt language education in the face of the challenges of the digital age. This research is expected to make a significant contribution to the understanding and application of good and correct Indonesian in daily life.